The Role of Future Generations in Place Branding: The Case of Huelva City - Xavier Ginesta; F. J. Cristòfol; Jordi de San Eugenio; Javier Martínez-Navarro (Politics and Governance, 2024)
The process of creating place brands must position the citizen at the center of the debate. The City Council of Huelva, a city in Southern Spain with a population of 142,538 inhabitants, promoted a territorial brand in 2022 in order to seek a new positioning for the city in tourism markets, investment, and talent attraction. Its development was based on a qualitative and quantitative methodology, previously tested out in other cities and locations in Spain, which is shaped by research groups, semi-structured interviews, and surveys of the citizens. This method aims to place the citizen, who ultimately is the user of the brand, at the center of the social research process that determines the tangible and intangible values associated with the brand narrative. The main objective of this article is to highlight, based on the case study of the brand Huelva Original, the importance of two groups in the construction and deployment of a place brand (Millennials and Generation Z and the political class). Firstly, out of the 1,194 people who participated in the fieldwork, 47.92% were under 40 years old. These two generations are crucial for creating a brand narrative that has long-term viability and presence in the digital environment. Secondly, the development of the brand narrative facilitated a cooperative process among the different political groups in the City Council, especially the two most represented (conservatives and social democrats), which enables the search for collaborative workspaces among political groups to ensure that the implementation of the brand transcends the term of a mandate and goes beyond short-termism political actions. The results indicate that the new brand uniquely differentiates Huelva, emphasizing internal pride and co-creation. Open innovation facilitates cooperation among stakeholders, improving governance. Both Millennials and Generation Z citizens, as well as politicians, are key to the long-term sustainability and reach of the brand.